Growth and Carrageenan from Kappaphycus alvarezii (Doty) at Different Depths and Their Possible Application in Other Locations - Wenno, Petrus A; Syamsuddin, Rajuddin; Jamal, Endang (Aquacultura Indonesiana, 2016)
This study aimed to evaluate the growth and yield of carrageenan from Kappaphycus alvarezii (Doty) which were cultured at different depths of water. The study lasted for 49 days, using two strains (green and brown), three initial weights (50, 100, 150 g), and five levels of depth (1, 2½, 4, 5½, 7 m). The results showed significant differences between growth rate and yield of carrageenan on the three treatments (P<0.01). The highest growth rate of both morphology types of green and brown occur on the same weight and depth i.e., at initial weight 100g and depth 2½ m, respectively at 5.68 and 6.05% day-1. The yield of carrageenan is likely to increase in depth with the highest value at a depth of 7 m, respectively 17.12% at green type and 14.63% at brown type. The results showed that reducing growth may increase the yield of carrageenan by the increasing of water depth. Based on these results, this study can be applied to another location as long as the quality of water allows farming activities.